Weed emergence as affected by maize (Zea mays L.)-cover crop rotations in contrasting arable soils of Zimbabwe under conservation agriculture. (March 2016) - Mhlanga, Blessing; Cheesman, Stephanie; Chauhan, Bhagirath Singh; Thierfelder, Christian
Abstract: Weed control in smallholder farming systems of sub-Saharan Africa is labour intensive or costly. Many researchers have therefore advocated for the use of cover crops in weed management as an affordable alternative for smallholders. Cover crops may be grown in rotations to suppress weeds and reduce the reliance on herbicides. The use of cover crops creates microenvironments that are either conducive or inhibitive to the emergence of certain weed species. A study, initiated in 2008 in contrasting soils at four different locations of Zimbabwe, investigated the effect of maize ( Zea mays L.)-cover crop rotations on the emergence of weeds that showed dominance in those soils. Weed assessments were however, carried out from 2011 to 2014. The weed species Galinsoga parviflora Cav., Commelina benghalensis L., and Richardia scabra L. showed dominance in all four locations with weed densities as high as 500 plants m −2 being recorded for R. scabra L. in a sandy soil. Maize-cover crop rotations resulted in higher densities of Bidens pilosa compared with maize monocropping (control treatment) due to its high nitrogen (N) requirement to produce more seeds. On the other hand, the integration of cover crops such as pigeon pea [ Cajanus cajan (L.) Millsp.] that had poor shading qualities, due to large gaps or spaces and slower initial growth, had limited effects on competitive weeds such as Cyperus esculentus L. which tend to dominate exhausted soils. The density of C. esculentus was 38% greater in maize–pigeon pea rotations compared with the control treatment. Variability between seasons and sites affected emergence of all weeds in the present study, which masked long-term trends. The results suggest that there is need to identify the germination and emergence requirements of specific weeds and select cover crops best suitable for their control. The study provides useful information for farmers and advisors on the best cover crops for control of certain problematic weeds in different soil types of Zimbabwe. Highlights: Rotating maize and cover crops has variable effects on the emergence of weeds. Variable weeds exhibit dominance in variable soil types and rainfall patterns. There is need to identify the most appropriate cover crop to control certain weed species.